ANTHELMINTHIC RESISTANCE (FASCIOLA HEPATICA) IN SHEEP AGAINST ALBENDAZOLE AND TRICLABENDAZOLE, LA PAZ - BOLIVIA - Mamani L., Willy (2009)
Fasciola hepatica resistance in sheep against albendazole and triclabendazole was evaluated in two farms in La Paz, Bolivia: one located near Tambillo (farm 1) and the other near Batallas (farm 2). Thirty male lambs of 7 to 8 months of age were selected in each farm. They were treated with 10 mg/kg of albendazole or 10 mg/kg of triclabendazole, and one group remained as non-treated. The gama glutamyl transpeptidase enzyme (GGT) profile and faecal eggs count reduction test (FECRT) were conducted. Lambs were slaughtered 8 weeks after treatment and the number of flukes in liver was counted. Minor reduction of GGT levels and faecal eggs count were observed in animals treated with albendazole. In the group treated with triclabendazole in farm 1 was observed a reduction of the GGT levels and faecal eggs count throughout the study, but not in farm 2. The reduction of flukes in liver lambs was 13.6 and 2.3% for albendazol in farms 1 and 2 respectively, and 98.0 and 36.3% for triclabendazol. It was concluded that anthelminthic resistance of F. hepatica to albendazol occurred in both farms, while in farm 2 resistance was gradually appearing to triclabendazole.